Urban terrorism - Masturah Alias; Ismail Ahmade; Sharifah Shahnaz Syed Husaine; Siti Mariam Abd. Aziz; Umminajah Salleh (University Publication Centre (UPENA), Universiti Teknologi MARA, 2009)
The book discusses the complex causes of terrorism and the diverse ideologies that could lead to the destruction of metropolises. The strategies urban areas are tremendously tempting targets for terrorists and the multiple mobility and technologies that sustain these areas are the very technogies and techniques that can be harnessed to destroy them.